Coats disease in infants, toddlers, and preschoolers: Clinical presentation and treatment outcomes - Saarang Hansraj; Subhadra Jalali; Vishal Raval (Indian Journal of Ophthalmology)
Purpose: To study the stage of presentation, clinical features, and treatment outcomes of patients diagnosed with Coats disease in infants, toddlers, and preschoolers (aged ≤5 years). Methods: A retrospective hospital-based study of 98 patients with Coats disease was conducted. Results: The mean age at presentation was 30 months (range, 4–60 months). Majority were males (n = 72, 73%) with unilateral presentation (n = 98, 100%). The most common stages at presentation were total retinal detachment (stage 3B; 36%), advanced end-stage disease (stage 5; 22%), and total retinal detachment with secondary glaucoma (stage 4; 16%). The most common cause of referral to our institution was Coats disease (n = 23, 49%), followed by retinoblastoma (n = 17, 36%). The most common presenting symptom was a white reflex (n = 49, 50%) or strabismus observed by the parents (n = 34, 35%). Treatment modalities included observation (n = 30 eyes, 31%), surgical intervention (n = 22, 22%), and laser photocoagulation ± cryotherapy ± intravitreal injection (n = 22, 22%). At a mean follow-up of 29 months (range, 1–100 months), the anatomical status of the disease remained unchanged in 35 eyes (36%), worsened in 18 eyes (18%), and resolved in 15 eyes (15%). Ten eyes (10%) underwent enucleation. At the last follow-up, two-thirds of eyes (n = 76) had visual acuity ≤20/400 and were categorized as blind. Conclusion: Coats disease in patients ≤5 years presents at an advanced stage (3B or more). At the last follow-up, the disease had stabilized in half of the eyes, whereas two-thirds of the eyes were blind, necessitating early diagnosis and treatment.